2021
DOI: 10.3390/jdb9030031
|View full text |Cite
|
Sign up to set email alerts
|

R-Spondin 3 Regulates Mammalian Dental and Craniofacial Development

Abstract: Development of the teeth requires complex signaling interactions between the mesenchyme and the epithelium mediated by multiple pathways. For example, canonical WNT signaling is essential to many aspects of odontogenesis, and inhibiting this pathway blocks tooth development at an early stage. R-spondins (RSPOs) are secreted proteins, and they mostly augment WNT signaling. Although RSPOs have been shown to play important roles in the development of many organs, their role in tooth development is unclear. A prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Most of these modes of molarization involve the modi cation of cingula to join or separate cusps to make the premolars less or more molariform. Modi cation of cingulum morphology is an intrinsically morphogenetic process relying on the interactions of enamel knots within a tooth (Cai et al 2007;Wang et al 2014;Dasgupta et al 2021;Sadier et al 2021). Morphogenetic models have demonstrated that small perturbations to the placement, timing, or resources available to enamel knots can drastically alter tooth form -single parameter changes in crown complexity evolution simulation software have shown the ability to gain or lose cingula in mammalian teeth (Salazar-Ciudad and Jernvall 2002Jernvall , 2004Jernvall , 2010Polly 2008).…”
Section: Perissodactyls and Independence Across The P4-m1 Boundarymentioning
confidence: 99%
“…Most of these modes of molarization involve the modi cation of cingula to join or separate cusps to make the premolars less or more molariform. Modi cation of cingulum morphology is an intrinsically morphogenetic process relying on the interactions of enamel knots within a tooth (Cai et al 2007;Wang et al 2014;Dasgupta et al 2021;Sadier et al 2021). Morphogenetic models have demonstrated that small perturbations to the placement, timing, or resources available to enamel knots can drastically alter tooth form -single parameter changes in crown complexity evolution simulation software have shown the ability to gain or lose cingula in mammalian teeth (Salazar-Ciudad and Jernvall 2002Jernvall , 2004Jernvall , 2010Polly 2008).…”
Section: Perissodactyls and Independence Across The P4-m1 Boundarymentioning
confidence: 99%
“…Moreover, tooth development can be blocked by inhibiting Wnt signalling via decreasing the expression of the Wnt activator R-Spondin 3 or increasing the expression of the Wnt inhibitor, Dkkl. 89,134,135 The ectopic expression of Wnt7b arrests tooth germ development, which is accompanied by decreased Shh expression. 99 In addition, the model of mouse incisor germ demonstrated the importance of the Wnt signalling pathway in tooth agenesis, even if it belongs to hypselodont instead of brachydont (such as teeth of humans and molar of mice).…”
Section: Tf Transcription Factormentioning
confidence: 99%
“…By comparing the geometric morphometry data obtained by advanced imaging—full skull cone beam computed tomography—of sex- and ethnicity-matched patients, these authors found that both the cleft and the malocclusion contribute to the extent of the craniofacial phenotype. Dasgupta et al [ 7 ] report that R-spondins, secreted proteins that augment Wnt signaling, are required for the formation of lower jaw incisors. Using compound mutant mice, they showed that simultaneous deletion of two members of the R-spondin family led to hypoplasia of the mandible and cleft secondary palate as well as severe dental abnormalities.…”
mentioning
confidence: 99%